Walter Spies and Pitamaha: Innovators Who Inspired the Development of Painting in Bali - Inten Asmariati, Anak Agung; Lestari, Sri (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2025)
The history of Balinese painting has undergone a long process of evolution, beginning with traditional wayang paintings used for ritualistic and palace decorations before transitioning into modern Balinese painting in the 1930s. Balinese painters hold a significant social status, as their works are deeply embedded in religious and cultural traditions. One of the key milestones in Balinese painting history was the establishment of the Pita Maha group, which played a crucial role in shaping artistic identity by fostering dialogue between local painters and foreign artists such as Rudolf Bonnet and Walter Spies. These interactions led to the emergence of a distinct aesthetic movement that combined traditional elements with new artistic expressions. This study examines the historical development of Balinese painting, emphasizing the impact of external influences such as colonialism, globalization, and modernization. Despite periods of disruption, Balinese painting has demonstrated remarkable continuity in its decorative aspects, themes, and use of traditional colors. The research also explores the transformation of Balinese painting from serving ritual functions to becoming a commercial art form due to the influence of tourism and Western artistic interventions. Using a qualitative descriptive narrative method, this research analyzes historical records, literature, and artworks to understand the evolution of Balinese painting. The study applies historical and social change theories to trace shifts in painting styles and their implications for Balinese cultural identity. Data collection includes primary sources such as historical texts and secondary sources including scholarly analyses of Balinese art. Findings indicate that while Balinese painting has retained core traditional elements, it has also adapted to external influences, particularly through the Pita Maha movement. The study highlights how Balinese artists navigate between preserving cultural heritage and adapting to modern artistic trends. Ultimately, this research underscores the dynamic interplay between tradition and innovation in Balinese painting, reflecting broader cultural transformations within Indonesian visual arts.